University tutoring: A pending task - Casanatán Miranda, Richard Américo (2018)
University tutoring is a new service that universities are offering their students. However, reality shows us that this service is still an attempt at trial and error, which does not go beyond good intentions because most of these attempts have not met the training objectives that were set. This article aims to explain the need to plan the tutorial work and institutionalize it as a program, which the university promotes with transversal objectives, from the first to the last university semester. For this to happen there must be a coincidence of concepts and achievements of the entire university community. Different researches confirm that graduated professionals know and demonstrate expertise in their specialty, however, the results are no longer auspicious when it comes to talking about human development and the management of social skills: lack of impulse control, adequate management of conflicts and lack of will development. It means, educated professionals, but people without training. A tutoring program, well articulated and systematized with appropriate topics to the personal needs of the student and the demands that society has on its professionals, will guarantee a complete training for the future professional. In other words, the university will stop being just an academic institution to become a human and integral development institution.